STRUCTURAL AND FUNCTIONAL CHANGES IN THE PROSTATE GLAND IN DIABETES MELLITUS - Hrytsuliak, B.V.; Hrytsuliak, V.B.; Bielova, N.V.; Hlodan, О.Ia.; Ivasiuk, I.Y.; Mykytyn, T.V. (World of Medicine and Biology, 2022)
Ultrasound scanning, colour ultrasound angiography, histology, morphometrics, and statistics were used to study the features of hemodynamics and the structural and functional state of the prostate gland in adult men with a history of insulin-dependent diabetes mellitus. Under these conditions, it was found for the first time that the peak arterial velocity in the central zone decreases to 6.20±0.38 cm/sec against 18.30±3.20 cm/sec in control and the peripheral area – to 2.70±0.01 cm/sec against 5.30±0.03 cm/sec. It was found that due to the proliferation of connective tissue in the prostate gland, its volume increases to 29.5±1.0 cm3, and weight – up to 27.4±1.5 g against 22.4±1.6 cm3 and 21.5±1.2 g, respectively, in men of the control group. The ratio between glandular parenchyma and muscular-elastic structure is 56 % and 44 % versus 69.8 % and 30.2 % in control, respectively. Histologically, prostate biopsy samples contained atrophic changes with a decrease in the lumen of the terminal glands, flattening of secretory epithelial cells, and proliferation of collagen fibres of the stroma. The testosterone concentration decreases to 380.0±12.0 ng/dL against 650.0±10.0 ng/dL in men of the control group.
Keywords: insulin-dependent diabetes mellitus; prostate gland; structural and functional changes